Yield and postharvest response of ‘Rosanna’ tomato to radiation-modified carrageenan and vermicompost tea - JAYRYL D. ENANO; MARILYN B. BALDERAS (Asian Journal of Agriculture, 2025)
Abstract. Enano JD, Balderas MB. 2025. Yield and postharvest response of ‘Rosanna’ tomato to radiation-modified carrageenan and vermicompost tea. Asian J Agric 9: 339-348. Tomatoes are one of the perishable crops, and inappropriate postharvest handling leads to a high amount of postharvest losses. The study investigated the effect of Radiation-Modified Carrageenan (RMC) and Aerated Vermicompost Tea (AVCT) on yield, fruit quality, and postharvest attributes in ‘Rosanna’ tomatoes. The study was laid out in a randomized complete block design consisting of seven treatments and three replicates and used the least significant difference test at a 5% level. Significant differences shown in fruit color at 20 Days from Initial Storage (DIS) (p = 0.0380); fruit firmness on 5 DIS (p = 0.0332), 15 DIS (p = 0.0099), and 25 DIS (p = 0.0291). Postharvest disease incidence at 14 DIS (p = 0.0115), 28 DIS (p = 0.0314); and postharvest disease severity index at 42 DIS (p = 0.0106), 56 DIS (p = 0.0416), and 72 DIS (p = 0.0297). No significant differences in other parameters; however, the 20,000 ppm RMC has the earliest day to harvest and the highest total yield. Fruits with the highest total soluble solids, titratable acids, and TSS/TA ratio at 40,000 ppm RMC + AVCT, 20,000 ppm RMC, and 20,000 ppm RMC + AVCT, respectively. The 1:1 (v:v) AVCT to water has the highest moisture and lowest dry matter. The highest fruit polar and equatorial diameter at 40,000 ppm RMC + AVCT. Fruits with the highest fruit color scale on 20,000 ppm RMC + AVCT at 5 DIS, and 20,000 ppm RMC at 10, 15, and 25 DIS. Firmer fruits in 1:1 (v:v) AVCT to water at 10 DIS, and 30,000 ppm RMC + AVCT at 20 DIS. The 10,000 ppm RMC + AVCT has the lowest percentage of disease incidence, the lowest severity index, and extended storage shelf life. The application of 10,000 ppm RMC + AVCT improved the fruit quality and extended the shelf life of the fruits.